Korelasi E-Literasi Terhadap Perilaku Pencarian Informasi Ilmiah di Internet oleh Mahasiswa Sekolah Tinggi Teknologi Payakumbuh - Dodi Nofri Yoliadi (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2022)
The purpose of this study was to determine the correlation between e-literacy and the behavior of searching for scientific information on the internet by students of the Payakumbuh High School of Technology. This research uses quantitative research methods. The variables of this study are: the independent variable is digital literacy (X) and the dependent variable is information retrieval behavior (Y) using the Simple Random Sampling Technique with a total of 221 students of the Payakumbuh High School of Technology. The results of the descriptive analysis test using the Mean and Grand Mean formulas obtained the results of digital literacy categorized as good with an average value of 3.23. Meanwhile, information seeking behavior is categorized as good with an average value of 3.21. Based on the product moment correlation test, the correlation coefficient between digital literacy variables (X) and information retrieval behavior (Y) was obtained at 0.824 at the coefficient interval between 0.80-1,000 indicating a very strong relationship, with a positive direction because the value of r indicates a positive number. . Furthermore, based on the results of a simple regression test for the X and Y variables, the equation Y = 18.010 + 1.438X and RSquare of 0.68 means that the relationship between digital literacy and information retrieval behavior is 68%. While other factors outside this study amounted to 32%. So it can be concluded that there is a correlation of e-literacy on the behavior of searching for scientific information on the internet by students of the Payakumbuh High School of Technology.